The complete chloroplast genome of Semiliquidambar cathayensis H.T.Chang ‘T5’ (Hamamelidaceae) - Xinghao Tang; Huihua Fan; Juan Zhang; Yu Huang (Mitochondrial DNA. Part B. Resources, 2020)
Semiliquidambar belongs to the family Hamamelidaceae and has comprehensive morphological traits between genus Liquidambar and Mushroom. There are three species of Semiliquidambar, all of which are endemic to China. Semiliquidambar cathayensis is the most widely distributed, from Fujian, Jiangxi to southern Guizhou, southeast and north of Guangxi, Hunan, and Hainan. Semiliquidambar cathayensis belongs to the Vulnerable (UV) in the China Plant Red Data Book. Semiliquidambar has been thought to be a product of natural hybridization but lacks convincing molecular evidence. In this study, the complete chloroplast (cp) genome sequence of an ecospecies S. cathayensis H.T.Chang ‘T5’, which has three leaf morphology, was determined using next-generation sequencing. The entire cp genome was determined to be 160,444 bp in length. It contained large single-copy (LSC) and small single-copy (SSC) regions of 88,969 and 18,913 bp, respectively, which were separated by a pair of 26,281 bp inverted repeat (IR) regions. The genome contained 133 genes, including 88 protein-coding genes, 37 tRNA genes, and eight rRNA genes. The overall GC content of the genome is 37.9%. A phylogenetic tree reconstructed by 13 chloroplast genomes reveals that S. cathayensis is most related with Liquidambar formosana in Hamamelidaceae with bootstrap support values of 100%.